Role of High-Dose Adjuvant Chemotherapy Followed by Autologous Stem Cell Transplantation in Locally Advanced Triple-Negative Breast Cancer: A Retrospective Chart Review. (30th September 2022) - Al-Share, Bayan; Assad, Hadeel; Abrams, Judith; Deol, Abhinav; Alavi, Asif; Modi, Dipenkumar; Kin, Andrew; Ratanatharathorn, Voravit; Uberti, Joseph; Ayash, Lois
Abstract : Purpose . Women with locally advanced/high-risk triple-negative breast cancer treated with the current standard chemotherapy continue to have a poor prognosis. High-dose chemotherapy with autologous stem cell transplant as treatment for locally advanced/high-risk breast cancer remains controversial due to a lack of survival benefit seen in previous phase III trials. However, these trials evaluated a heterogeneous group of patients with different receptor subtypes. A marginal benefit was observed in certain subgroups. We report long-term outcomes of women with stage IIB or III triple-negative breast cancer treated with high-dose chemotherapy followed by autologous stem cell transplant at our institution between 1995 and 2001. Methods . This is a retrospective analysis of stage IIB or stage III triple-negative breast cancer treated with high-dose chemotherapy followed by autologous stem cell transplant. We excluded women with hormone-positive, HER2/neu-positive/unknown, and/or metastatic disease prior to transplant as per updated AJCC 7 th edition guidelines. Patients underwent surgery and either neoadjuvant or adjuvant anthracycline and taxane-based chemotherapy and then proceeded to high-dose chemotherapy and autologous stem cell transplant using carmustine 600 mg/sqm, cyclophosphamide 5.6gm/sqm, and cisplatin 165 mg/sqm (STAMP 1 regimen) for consolidation. This was followed by locoregional breast and lymph node radiation per standard of care. Results . Twenty-nine women (2 stage IIB and 27 stage III) were evaluated. The median age at diagnosis was 43 years (IQR: 40, 51). Eleven patients had 4–9 regional lymph nodes (LN) involved and 16 had 10+ involved LNs. Four patients had T4 or inflammatory breast cancer and two had ipsilateral supraclavicular LNs involved. The median follow-up time is 16 years (95% CI: 12, 19, range <1–19 y) posttransplant. The median overall survival was 15 years (95% CI: 3, 19); the median DFS was 14 years (95% CI: 1, 19). Conclusions . This study of locally advanced/high-risk triple-negative breast cancer treated with adjuvant high-dose chemotherapy and autologous stem cell transplant reveals high overall survival rate. With the current improvement in treatment-related mortality, re-evaluating this approach in this subset of high-risk breast cancer in prospective randomized studies may be worthwhile.